A Finite Control Set Model Predictive Control Algorithm With Low Complexity for Neutral-Point Clamped Converters With Switching Constraints - Schuetz, Dimas A. (2024)
This paper proposes a Finite Control Set Model Predictive Control algorithm with low complexity for three-phase grid-tied Neutral-Point Clamped converters with switching constraints. The system model is represented in the converter output line-to-line voltage coordinates, where the voltage vectors are integer values. First, the unconstrained solution is obtained to control the converter-side currents. Ellipse constraints are inscribed in the Space Vector diagram to ensure the switching transitions between only adjacent levels in the phase voltages. Moreover, the inverter voltage vector to be implemented in the next sampling period is obtained with low complexity by rounding the constrained voltage vector. Afterward, a cost function is calculated for the redundancies of the chosen inverter voltage vector, aiming to balance the DC-link capacitor voltages. The proposed algorithm presents advantages such as low computation burden, fast transient response, and good steady-state performance. Real-time Hardware-in-the-Loop results are presented to demonstrate the good performance of the proposed algorithm compared to other techniques with a reduced computational burden. Moreover, experimental results show the effectiveness of the proposed algorithm in terms of transient response and steady-state performance.